Analysis of Integrating 240 MW Wind Power Plant into Azerbaijan Power Grid - Zalov, Nihad (ADA University, 2023)
Azerbaijan has consistently depended on traditional fossil fuels to provide its energy requirements over the course of its history. This is despite the fact that the country possesses massive oil and gas reserves. On the other hand, in view of the growing concerns that are being expressed on a global scale regarding climate change and the necessity of expanding energy supplies, the majority of governments all over the world are concentrating their attention on renewable energy sources (RES). Azerbaijan has also committed to fulfilling a large obligation to make a contribution to the mitigation of climate change and to incorporate thirty percent of its energy production into environmentally friendly energy sources. The aim of this study is to examine the necessary conditions that need to be fulfilled in order to integrate a 240megawatt wind power facility into Azerbaijan's electrical grid. This investigation makes use of technical network analysis in order to investigate operational voltage levels in relation to the connection of generation to the power system at the local point of interconnection (POI). A thorough investigation and evaluation will be carried out on the voltages and power flows that are present at the substations that are connected to the wind power facilities. The Short-Circuit Ratio, often known as the SCR, is an important quantity that is applied in the process of determining power system resilience and stability. One crucial factor to think about is the integration of alternative energy sources like solar plants and wind farms. An extensive examination will be conducted to determine the levels of SCR at both substations where the wind farms are connected
Keywords: Renewable energy sources -- Azerbaijan -- Wind power; Wind power -- Integration -- Azerbaijan; Energy policy -- Azerbaijan -- Renewable energy; Solar energy -- Integration -- Azerbaijan; IT and Engineering